“We Need to Think about the Grammar”: Practices for Opening Explanations on Language and Changing their Linguistic Focus - Mark Romig (Studies in Applied Linguistics & TESOL)
Although the role of grammar instruction is still highly debated within the field of second language acquisition and language pedagogy (Nassaji, 2017), explanations have emerged as fruit-bearing interactional phenomena that can illustrate the “how” of explicit grammar instruction (Fasel Lauzon, 2015; Hudson, 2011; Majlesi, 2018; Matsumoto & Dobs, 2017; Ro, 2021; Romig & Horan, 2023; Rosborough, 2011; Smotrova, 2014). A key feature of explanations is their sequential organization, described by Fasel Lauzon (2015) as consisting of an opening, a core, and a closing. In a nutshell, openings involve some problematization of prior talk, cores provide a candidate solution to said problem, and closings involve acceptance of that candidate solution. Researchers have revealed much about how cores are delivered, particularly focusing on how grammatical concepts can be illustrated through a variety of multimodal resources (Hudson, 2011; Matsumoto & Dobs, 2017; Romig & Horan, 2023; Rosborough, 2011; Smotrova, 2014), but less attention has been paid to openings and closings. This is perhaps unsurprising given that the bulk of content is delivered in an explanation core, but knowing how to open grammar explanations can be of particular importance for teachers in training who may not know when an explanation is due or how to initiate one themselves. Additionally, there does not seem to be any research detailing how to make clear that an explanation of a particular language point is grammatical, and not about any other linguistic issue (e.g., meaning, pronunciation, etc.). Thus, this paper adopts a conversation analytic framework to examine how a teacher opens an explanation sequence on the use of “so” and ensures that it is about its grammatical role as a coordinating conjunction, not on its meaning.